2007
DOI: 10.2337/dc07-0015
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Therapy Ameliorates Fasting and Postprandial Lipoproteinemia, Oxidative Stress, and the Inflammatory Response in Subjects With Hypertriglyceridemia and the Metabolic Syndrome

Abstract: OBJECTIVE -The aim of this study was to determine the effects of fenofibrate (160 mg/day) on fasting and postprandial lipoproteins, oxidized fatty acids, and inflammatory mediators in subjects with hypertriglyceridemia and the metabolic syndrome.RESEARCH DESIGN AND METHODS -Fifty-nine subjects with fasting hypertriglyceridemia (Ն1.7 and Ͻ6.9 mmol/l) and two or more of the Adult Treatment Panel III criteria for the metabolic syndrome were randomly assigned to fenofibrate (160 mg/day) or placebo in a double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 42 publications
4
68
1
2
Order By: Relevance
“…In the setting of metabolic syndrome and hypertriglyceridemia, fenofibrate was shown to be more effective in reducing fasting triglyceride and increasing HDL cholesterol levels and in reducing postprandial triglyceride levels and oxidized fatty acid levels, which corresponded with a decrease in VLDL particle size and an increase in LDL particle size (21).…”
Section: Effects Of Fenofibrate In Marked Dyslipidemiamentioning
confidence: 99%
“…In the setting of metabolic syndrome and hypertriglyceridemia, fenofibrate was shown to be more effective in reducing fasting triglyceride and increasing HDL cholesterol levels and in reducing postprandial triglyceride levels and oxidized fatty acid levels, which corresponded with a decrease in VLDL particle size and an increase in LDL particle size (21).…”
Section: Effects Of Fenofibrate In Marked Dyslipidemiamentioning
confidence: 99%
“…However, analysis of two haplotypes that only differ for 3u2131CϾT showed marginally significant difference of plasma CRP levels (P ϭ 0.09), suggesting that the effect of this SNP may be subject to the haplotypic context. Studies have shown that fenofibrate along with other fibrates lowers inflammatory markers such as CRP in patients with dyslipidemia associated with insulin resistance, obesity, and the metabolic syndrome (17,18). The anti-inflammatory action is mediated by the activation of peroxisome proliferator-activated receptor ␣ (PPAR-␣), which functions as a negative regulator of genes involved in the inflammatory response by antagonizing the activity of transcription factors such as nuclear factor-B and activator protein-1 (19).…”
Section: May 2008mentioning
confidence: 99%
“…Fenofibrate, a PPAR-ligand, has been demonstrated to reduce TG levels in fasting and postprandial states in a cohort of hypertriglyceridemic subjects with MetS; this TG-lowering effect resulted primarily from reductions in fasting and postprandial concentrations of large and medium VLDL particles 17) . Moreover, fenofibrate has been shown to reduce non-fatal myocardial infarctions and coronary revascularizations in diabetic patients 18) .…”
Section: Introductionmentioning
confidence: 99%